Evaluasi Potensi Tepung Tubifex sebagai Pengganti Tepung Ikan dalam Pakan Benih Ikan Nila (Oreochromis niloticus) - Yusup, Dandi Diana; Simangunsong, Tohap; Sukardi, Purnama (Jurnal Perikanan Unram, 2025)
The high cost and limited availability of fishmeal in aquaculture feed formulations have prompted the search for sustainable and affordable alternative protein sources. This study aimed to evaluate the effects of substituting fishmeal with silk worm (Tubifex sp.) meal on the growth performance, feed utilization, and survival rate of Nile tilapia (Oreochromis niloticus) fry. A completely randomized design (CRD) was used with four dietary treatments: P1 (control, 0% Tubifex), P2 (15%), P3 (25%), and P4 (35%), each with three replications. Fish were fed twice daily for 30 days, and growth parameters were measured weekly. Results showed that the inclusion of Tubifex meal significantly improved the final weight, specific growth rate (SGR), average daily gain (ADG), and feed efficiency (FE), particularly in P3 and P4. The highest SGR (2.28%/day), ADG (0.016 g/day), and FE (61.93%) were recorded in the P4 group. Survival rate also improved, reaching 82.22% in P4 compared to 51.11% in the control. Water quality parameters remained within optimal ranges, indicating no adverse environmental impact from Tubifex inclusion. The findings suggest that Tubifex meal is a viable protein source that can replace fishmeal by up to 35% in tilapia fry diets. Its application offers nutritional, economic, and ecological benefits, making it a promising component in sustainable aquafeed development.